Are we all Human? Anti-Colonial Consciousness and Critique of Humanism - Bhattacharya, Riya (Kent Law Review, 2022)
Are we all Human? Anti-Colonial Consciousness and Critique of Humanism Introduction “I place my ear upon the ground And listen to the earth of Africa, Voices rise from Uganda; from Mozambique In South Africa, pink-soled feet shatter their chains in fury” — Tanganyika Reportage Nazim Hikmet “Before dropping off to sleep he thought: the face of the French cop…the face of the Nazi torturer at Buchenwald and Dachau, the face of the hysterical mob at Little Rock, the face of the Afrikaner bigot and the Portuguese butcher in Angola, and, yes, the black faces of Lumumba’s murderers—they were all the same face. Wherever this face was found, it was his enemy; and whoever feared, or suffered from, or fought against this face was his brother.” —The Stone Face William Gardner Smith “It is a bitter and tragic fact that, for the Europeans in Algeria, being a Man means first and foremost superiority to the Muslims…[they need] to humiliate them, to crush their pride and drag them down to animal level…It is Man himself they want to destroy, with all his human qualities…the very qualities the coloniser claims for himself” —Introduction to Henri Alleg’s The Question Jean-Paul Sartre “I accept internationalism only when Africa and Asia can be free to choose on par with those 500 million in the colonial countries. In that case I will accept it as humanism, meaning the true equality of humanity. However, as long as I am not a human being, and I am accused of being ‘primitive’, I cannot do anything. The Westerner’s relationship with me will be like a slave-foreman relationship, or an empty-handed man with a capitalist. The former should toil, so the latter can get all the profit”. —The mission of the free thinker in society Ali Shariati (trans. Fatollah Marjani) In the last quote above, Shariati uses the number “500 million” in order to echo something that Sartre had stated in his famous preface to Fanon’s “The Wretched of the Earth” (Sartre/Fanon, 2001, pg.7). Sartre, the key thinker of French existentialism, and an intellectual inspiration for both Shariati and Fanon, had critiqued what we may term ‘classical’ European humanism sixteen years before writing the preface, arguing that it is the basis for a “cult of humanity”, an ideology that eventually gives way to fascism (Sartre, 2007, pg.52). Yet it is with the arrival of Fanon and the brutality of the Algerian liberation war that Sartre expands this thought and pays attention to the use of ‘humanism’ outside of Europe’s borders, with its relationship to colonial domination (Sartre/Fanon, 2001, pg.21-23). The earth had been divided into two: “five hundred million men, and one thousand five hundred million natives” (Sartre/Fanon, 2001, pg.7). Just as Fanon describes the native who “discovers reality and transforms it…into his plan for freedom” (Sartre/Fanon, 2001, pg.45), Sartre’s statement captures a sort of awakening to reality for those who choose in the colonial centres who chose (or were elsewise unable to avoid) to listen to the newfound voice of the third-world; to see colonialism for what it really is. The colonised, the “others who become men in name against us (the coloniser)”, strip European humanism down from its abstract notions and reveal it to be “nothing but an ideology of lies, a perfect justification for pillage…its affections of sensibility only alibis for our aggressions” (Sartre/Fanon, 2001, pg.21-22). European humanism was revealed to be, according to Sartre, a “racist humanism, since the European has only been able to become a man through creating slaves and monsters” (Sartre/Fanon, 2001, pg.22). This has a duel meaning: “Europe is literally a creation of the third world” not only materially, but also European ‘Man’ is a creation that only exists in relation to the defining of the colonised as ‘natives’ (Sartre/Fanon, 2001, pg.81). The exploited workers of the first world were nevertheless given the ‘human’ status, whereas the colonised had to be reduced to the status of “superior monkeys” (Sartre/Fanon, 2001, pg.13). The European was able to justify their non-human treatment of the colonised, their enslavement, forced labour and torture, via Man, having ownership over the natural world-separate from the human being (Sartre/Fanon, 2001, pg.13). The so-called “monkeys” were just like the raw materials of the Earth - free to be extracted and exploited. Yet at the same time they can never fully be dehumanised, for “to be able to give them orders, to get them to work, however brutal the regime, their basic humanity has to be acknowledged” (Majumdar, 2007, pg.93). Humanism is, therefore, inherently paradoxical. It is based as much on defining the human and giving one human status as it is on denying the undeniable humanity of the other. The contradiction of “laying claim to and denying the human condition at the same time” is, as was shown by the Algerian war of independence, an explosive one (Sartre/Fanon, 2001, pg.17). Denying the equality of the colonised long reduced humanity to, as Cesaire so accurately put it, a “mere monologue” (Cesaire, 2000, pg.74). Levinas summarised this standpoint succinctly: “Humanity consists of the Bible and the Greeks. All the rest can be translated: all the rest-all the exotic-is dance” (Dabashi, 2019, pg.65). Within and following the anti-colonial moment however, there has been a growth of decolonial thinkers who have forcibly broken the monologue, giving voice to long needed critical reflection. How the “human” is defined, who defines it, for what it is defined, and against what, are just some of the questions such thinkers have taken up. We will be exploring these same questions, illustrating the striking contradictions inherent in the abstract notion of the ‘human’ and the realities of history. We will attempt to show why thinkers such as Walter Mignolo have demanded “epistemic disobedience”, not only to enrich the world with knowledge that is just as legitimate and valuable (if not more so) than so-called ‘European knowledge’, but also because the epistemological underpinning of European notions of the ‘human’ are, far from being universal, in actual fact invalid and exclusionary (Mignolo, 2011, pg.282). Most importantly, in order to attempt to answer these questions, we are going to have to investigate what may seem a separate question, yet is anything but. We have to explore the question surrounding the ‘universal’, for it is the study and critique of the imposed ‘universality’ of European Man that once lied at the centre of the flourishing anti-colonial of anti-colonial consciousness, and which now lies at the centre of the decolonial project. In setting out on this task, it is important that we distinguish between what Sylvia Wynter has termed “Man1”, the human defined during the European Renaissance, and “Man2”, the human defined during the European Enlightenment (Wynter, 2003, pg.264). We will be assessing the decolonial critiques of both whilst also illustrating their common ground, before discussing the “Man” that still pervades our understanding of the ‘human’ today. Man 1 In 1550, during the Valladolid debate, Ginés de Sepúlveda relied on an Aristotelian text in order to philosophically argue that the indigenous peoples of the America are not human, but “slaves by nature” (Dussel, 2011, pg.236). This reference to the works of the long dead Aristotle for a source of authority is a moment which captures the 15th and 16th centuries of European Renaissance. The Renaissance was the re-discovery of the past; of Greco-Roman antiquity, with its art, literature, science and history (Mandrou, 1978, pg.40-54). More than this, it was the changing of Christian self into the Rational self. It was the changing of society via a new-found connection to a past which became claimed as ‘European’ (Mandrou, 1978, pg.40-54). So, it may seem strange to centre a discussion on what some have titled the “true European legacy” of modernity outside the ever-shifting borders of Europe (Mignolo, 2002, pg.89). The European encounter with the Americas is, for the decolonial thinkers, essential to understanding the way in which the ‘human’ was defined, yet in most European narrations of history, it is almost never reflected upon (Saffari, 2019, pg.289). At best, one may find in such works a brief mention of the way renaissance humanism was “powerfully reinforced by the European discovery of non-Western societies” (Nauert, 2008, pg.222). Yet, contrary to Eurocentric presentations of history, neither ‘modernity’ nor the Renaissance are “exclusively European products” (Saffari, 2019, pg.289). On the one hand, the Renaissance’s intellectual developments were only possible with the contributions of “earlier Muslim scientists, philosophers, and theologians including al-Razi, al-Farabi, Ibn Sina, al-Ghazali, and Ibn Rushd”, who not only translated the classical Greek and Roman texts that became the basis of the Renaissance, but also provided endless commentaries on their work (Saffari, 2019, pg.289). On the other hand, the Renaissance, and in particular its humanist ideology, is fully formed only out of (to put it kindly) interaction with the world outside of Europe. The Renaissance (and European Modernity at large) are, as Dussel states, “not exclusively European”, but instead a product of the “continuous dialectic of impact and counter-impact, effect and counter-effect, between modern Europe and its periphery” (Dussel, 1996, pg.131). Sepúlveda’s statement exemplifies this very happening. He is not, of course, in discussion with any indigenous peoples, but it is only with the colonial encounter with the ‘other’ that he is able to flesh out a definition of the human. Previously, the “physical referents of the conception of the Untrue Other to the True Christian Self” had been defined as “heretics” (Wynter, 2003, pg.266). Yet, “in the wake of the West’s reinvention of its True Christian Self in the transmuted terms of the Rational Self of Man1”, it was to be the people of the newly colonised world that were “made to reoccupy the matrix slot of Otherness” (Wynter, 2003, pg.266). To put it simply, the humanism of the Renaissance is, as Wynter points out, based on a “redescription of the human as the rational, political subject, ‘Man1’— on the basis…of their parallel invention of Man’s Human Others…[the] irrational animals”. (Wynter, 2003, pg.315). So, the “invention of Man”, as Michel Foucault terms it, is born out of a power struggle on behalf of the newly emerging European colonial states (such as Spain and Portugal) and their (still religious) intellectuals, against the almighty political power of the Church (Wynter, 2003, pg.263). The Renaissance humanists “epochal redescription of the human outside the terms of the then theocentric, ‘sinful by nature’ conception/ “descriptive statement” of the human” was the method by which the humanists sought to bypass the authority of the Church (Wynter, 2003, Pg.263). By reconfiguring the idea of the ‘human’ outside of the Church’s definition, humanism was in a sense rebelling against “the hegemony of the Church/clergy over the lay world of Latin-Christian Europe”, which had, up until then, been “supernaturally legitimated” by the naturally sinful understanding of the human (Wynter, 2003, pg.263). With this partial liberation from the church’s authority, the humanists gained the power to define who was and what made up the human, but crucially, they also got the power to decide who wasn’t and what couldn’t be human (Wynter, 2003, pg.263). The latter half of this power is often left unsaid, yet it should be clear and obvious for all to see. Its origin is within those very texts upheld as being the original shining light of ancient humanism. As Dussel states, we must remember that “Greece and Rome were slave civilisations of a cruelty without equal, hidden only by a distorted interpretation under the Western philosophical mantle of ‘Hellenist Humanism’…of modern European ‘classic’ culture” (Dussel, 2011, pg.236.) As a final point, whilst we will soon come to see that the creation of ‘Man2’ really establishes the classifications of the ‘human’ and instils the hierarchical relationship between the human and the ‘non-human’, even during the Renaissance, one can begin to see this trend develop. Whilst the humanists (in particular in the Spanish context) were often less bold in declaring their right to rule as regards to them being the superior natural beings, they did nevertheless categorise the peoples of the world with systems of ranking. Dussel points to Jose de Acosta for an example, explaining that the Spaniard in Peru was closer to the judgement of Vittoria than Las Casas with regards to the Valladolid debate, for whilst he did not agree entirely with the argument of Sepúlveda, he did agree that the ‘Christianisation’ of the Americas was entirely valid (Dussel, 2011, pg.224). His reasoning for thinking in this way is his classification of the indigenous peoples of America as ‘barbarians’ (Dussel, 2011, pg.224.). Yet Acosta does not merely differentiate the indigenous peoples from himself by transforming them into the singular ‘Other’ of the European Human; he also illustrates an understanding of the world external of (and hence under the thumb of) Europe as being divided into various categories of ‘barbarian’ (Dussel, 2011, pg.225). Dussel expertly discusses Acosta’s three categories of ‘barbarians’ placed in a hierarchical order: At the top are the Indians and the Chinese, for they supposedly don’t strain too far from “straight reason and the general purpose of mankind”, and also for the organisation of their cultural and political systems which at least in some form mirror that of the European, and are also importantly assessed to retain some form of ‘knowledge’ (Dussel, 2011, pg.225). Of course, the European overseer is quick to dismiss the epistemologies of the rest of the world, but in this case, they are at least courteous enough to admit that these barbarians aren’t completely incapable. The second ranked ‘barbarians’ (which includes the Peruvians) are afforded no such praise, supposedly having no ‘knowledge’, but nevertheless, they retain political systems which are in some way familiar, and hence, they aren’t at the bottom of the pile (Dussel, 2011, pg.225). That spot is reserved for those (such as the Caribbeans) who are “similar to animals…they hardly have any human feelings” (Dussel, 2011, pg.225). This precursor to the biological and anthropological knowing of the world pushed by some of the most significant Enlightenment thinkers (in particular Kant) is important for us to remember, for as useful as Wynter’s understanding of ‘Man1’ and ‘Man2’ are, we may be mistakenly lulled into believing that there is a strict dividing line between the two. In reality, whilst the Enlightenment thinkers do often radically break with the thinkers of the Renaissance, they do build upon and often assume the knowledges that the Renaissance thinkers created. Dussel argues against the idea that modernity began with Cartesiansim or Kantian critique, arguing instead that it begins with the colonial voyage to the Americas, and the subsequent consolidation of colonial power in the rest of the world (Saffari, 2019, pg.289). Similarly, I would argue that the ‘human’ as we know it today has its roots in the colonisation of the Americas, and that, although it has developed much since then, it nevertheless has its roots there. ‘Man2’ is, I would argue, latent within ‘Man1’. Man 2 “Kant’s anthropology and geography offer the strongest, if not the only, sufficiently articulated theoretical philosophical justification of the superior/inferior classification of “races of men” of any European writer up to this time” —Emmanuel Eze (1997, pg.12) If the Renaissance was the beginning of the ‘human’ end of, then the Enlightenment was its fulfilment. The titans of Enlightenment, as they are often called, most famously Kant, are said to have “invented the “human” in particularly poignant and powerful and all- knowing terms”, and ever since, European philosophers and scientists has deemed it necessary to reply with a statement of approval or disapproval (Dabashi 2012, pg.19). Within Germany alone there are more than enough famous followers of Kant who proceeded to challenge his humanism with a form of anti-humanism (see Nietzsche and Heidegger in particular) (Dabashi 2012, pg.19). To follow the decolonial project however, we must avoid entering into these monologues and instead engage with the seeming problem of contradiction inherent within Kant’s universalism and Kant’s anthropological understanding. I shall begin with a famous quote from Marx before delving into ‘Man’ as Kant understood him. “The eighteenth-century individual—the product on one side of the dissolution of the feudal forms of society, on the other side of the new forces of production developed since the sixteenth century—appears as an idea, whose existence they project into the past.” —Grundrisse, Karl Marx (1973, pg.17) We should, of course, add to Marx’s analyses that by the eighteenth century individual, he is really referring to the eighteenth-century European individual. ‘Man2’, or the human as the Enlightenment European envisaged it, is a creation that became naturalised, rather than a natural being that came to be ‘discovered’ (Serynada, 2015). Europe “invented Man and projected Him onto the past as a natural and timeless [being]”, which therefore takes away the reality of humans being a product of their societies’ historical and cultural development (Serynada, 2015). Whilst Marx takes particular aim at the political economists (most notably Adam Smith) who propounded this inaccurate way of thinking, Wynter makes sure to add that Darwinism too had a role to play (Wynter, 2003, pg.314). The combination of these and other forms of thinking “articulated and universalized a version of the human driven by the imperative of survival and perfectly embodied in Western Man” (Serynada, 2015). What the European thinkers had created now became naturalised, and in becoming naturalised it became justified and inevitable. The ascent of Western Man to a position of domination over the world (and to a position of over-representation as Wynter said) became a fact of biological evolution, and their quest for power became a fact of nature (Serynada, 2015). None other than the mature Kant himself expressed this point when he said: “Thanks be to Nature, then, for the incompatibility, for heartless competitive vanity, for the insatiable desire to possess and to rule! Without them, all the excellent natural capacities of humanity would forever sleep, undeveloped”. (Kant, 1963, Fourth Thesis) Within this very statement there are two intertwining points we must draw out. The first is the most obvious, namely, to question whether humanity at large did have such a desire, and whether this is a natural capacity of humanity? The European enlightenment’s rereading of history may suggest such a thing, but does that necessarily mean that this statement is true for all societies across all ages? Or is it an all too expected example of Eurocentrism, which, at its core, “is the attribution of theoretical significance to European historical experiences…the universal is the generalizable European concrete”. (Ghamari-Tabrizi, 2016, pg.xiii) The second point is more subtle but just as important. In saying that the “desire to possess and rule” is a natural characteristic of Man, Kant not only paves the way for calling those who don’t to be “non-human”, he also paves the way for hierarchy within the definition of humanity: every ‘human’ may want to possess and rule, but not every human has achieved this natural aim in the same way as the European-the European is thus more human than the rest of those it rules over (Serynada, 2015). Colonialism is therefore justified under the pre-text that it is a natural human development, that every society had wished to achieve it, and in actuality not achieving it is simply as a result of their inferiority. As Kant explicitly states: “Humanity is at its greatest perfection in the race of the whites" (Eze, 1997, pg.58). It is perhaps necessary to show to just what extent this dehumanises all ‘Others’ on the planet with a few excerpts from Kant. There is not enough time to trawl through his categorisation and ordering of the people of the world in his reprehensible Observations on the feeling of the Beautiful and the Sublime, but we can mention that his hierarchy of people is far worse than anything Acosta ever wrote (Kant, 2011, pg.13-62). At his ‘best’, Kant completely dismisses all Indian and Chinese art, stating all their artistic achievements are “grotesquries”, an inevitable result of their “adventurous taste”, that their art is unable to mirror nature and is therefore worthless (Kant, 2011, pg.21). Of course, he doesn’t stop for one second to consider whether there could be any value within such art, why would he? He could never imagine that perhaps the arts of other cultures can be a practice of “imitating precisely what is beyond the tangible, beyond nature, in order to decorate nature in its image, or to make something the human being longs for in nature but does not find” (Shariati, 2011, pg.18). At his worst, Kant is beyond ignorant: “Negroes . . . have by nature no feeling that rises above the ridiculous” and “not a single one has ever been found who has accomplished something great” (Kant, 2011, pg.58). If one is “completely black from head to foot”, then that for Kant is “distinct proof” that what they may think or say is “stupid” (Dabashi, 2019, pg.60-61). One doesn’t need to be able to read between the lines in order to realise that Kant is racist. The important question to ask is what possible reasoning is there behind Kant’s being able to think this way? How can Kant simply deny the humanity of the majority of the world? How is it that Kant, the thinker of universalism, can believe and think in such a way that Al-Biruni once critiqued in the 11th century? How can Kant believe and confidently state that there is “no other race of man [worthwhile] but theirs (his), and no created beings besides them have any knowledge or science whatsoever”? (Al-Biruni, 1910, pg.23) How is it that Kant does not think that the non-European is a ‘man’, a knowing subject? The answer, in my reading, lies solely in ‘power’ and ‘domination’. The decolonial critique illustrates how, as one writer put it, “what is called ‘anthropology’ or ‘ethnography’ etc. have all been there because world conquerors needed to know [and define] the people they were going to rule” (Dabashi, 2021, pg.1). Kantian universalism has, within it, and at its foundation, an inescapable, hierarchal power dynamic. When Kant speaks of the universal, he is speaking of something that does not yet exist. To borrow from Cesaire, Kant’s humanism is not “made to the measure of the world”, rather it encloses the world, squeezing it within his tight framework (Cesaire, 2000, pg.73). Kant’s universal is one that “presupposes a single culture, a single religion, a “world-wide” conformism” (Gramsci, 1999, pg.703). To achieve Kant’s universal, the European must, through coercion, brutality and displacement, demand that the rest of the world submit to them. So, universalism is not flat, it is instead incredibly hierarchal and indeed, vertical. To be universal in this way is to either demand that all others in the world surrender themselves to you, or, it is to surrender oneself up to the universal, in order to be shaped by it. ***************************************** In the middle of a long note in his Second Discourse, Rousseau remarks that “the entire world is covered with people of whom we know only their names, and yet we amuse ourselves judging the human race!” (Rousseau, 1984, Pg.160). Out of context, this might sound like a critique of European colonial entitlement, but in reality, Rousseau is demanding more from what he perceives as a lacking knowledge production from the colonial powers. In his eyes, Europe needed more Diderot’s, Montesquieu’s and D’Alembert’s to visit the colonial worlds’ peripheries in order to produce this supposedly desperate need for knowledge (Rousseau, 1984, pg.161). He places total faith in such figures, going as far as to say that “if such observers…were to assert of an animal that it is a man and of another animal that it is a beast, then I say we must believe them” (Rousseau, 1984, pg.161). Think of the power dynamics held within that very sentence. Rousseau is, knowingly or unknowingly, asserting that the European is in a position of responsibility, where they can stand above the world, surveying it from up on high, telling its inhabitants whether they are human or whether they are animal. Being in part an anthropologist, Kant’s own academic practice reflects this power dynamic that Rousseau spells out. The non-European is his object of study: they cannot think for themselves, for if they do then, according to Dabashi, there is a serious fault in his philosophical project (Dabashi, 2019, pg.60). As Souleymane Bachir Diagne argues, “Europe finds in its anthropological vocation the justification for its capacity to understand the others better than they ever understood themselves” (Diagne, 2020, pg.23). Europe raises itself to a level above human, to a position of power where it can potentially push everyone it has conquered into the level of animals. European intellectuals ability to do this provides them with an all-dominating power. It allows the European “to provide orientation for the rest of humanity [the non/lesser humans]” (Diagne, 2020, pg.23). It is for this reason that Kant can so flippantly remark that “the enlightened nations…will probably give law, eventually, to all the others” (Kant, 1963, Ninth Thesis). Such delusions allow one to think that it is only reasonable that these colonial shepherds must lead their flock. How burdened they must have felt. When one reads these words, it is hard not to remember Edward Said’s Orientalism. Of particular relevance is his analysis that “knowledge of the Orient, because generated out of strength, in a sense creates the Orient, the Oriental and his world” (Said, 1979, pg.40). In much the same way that the ‘human’ was invented, so too its ‘Other’. The ‘Other’ for Man2 is, I would suggest, the ‘native’. As Mahmood Mamdani asserts, “the native is the creation of the colonial: colonized, the native is pinned down, localized, thrown out of civilization as an outcast, confined to custom, and then defined as its product” (Mamdani, 2012, pg.2). The ‘native’ is not then, as is commonly thought, an authentic mode of being. It is instead a fictive creation. There’s an incredible irony here. Kant famously stated in his short essay What is Enlightenment? that there should be no restrictions on an individual’s attempt to achieve enlightenment within their own society. To quote directly: “If only they refrain from inventing artifices to keep themselves in it, men will gradually raise themselves from barbarism” (Kant, 1784, Para 8). In the case of the colonised, the ‘lesser’ humans, Kant and other anthropologists invented these artifices. They invented the idea that these peoples around the world had timeless, unchanging essence and a forever lasting inferiority. Once again, the dynamic humanity of such people is denied, they instead have to remain as static objects to be studied and extracted from. They have to remain unmoving, they are “never a subject in communication”, they are always an “object in information” (Foucault, 1995, pg.200). To limit human beings within these frameworks is also to limit their room for action, and hence, for rebellion against the colonial/neo-colonial order. As one author put it: “I am saying that I, as an Asian, or an African, am supposed to preserve my manners, culture, music, religion, and so forth untouched, like an unearthed relic, so that the gentlemen can find and excavate them, so they can display them in a museum and say ‘Yes, another example of primitive life’.” (Al-Ahmad, 1984, pg.34) Conclusion When Gramsci wrote on Kant, he engaged critically with a mistranslation of the categorical imperative. In his reading, Kant’s ethics demanded that one “must act according to a ‘model’ which he would like to see diffused among all mankind, according to a type of civilisation for whose coming he is working or for whose preservation he is ‘resisting’ the forces that threaten its disintegration” (Gramsci, 1999, pg.703). The final part of the sentence seems almost prophetic when one witnesses the post-colonial situation. The independence of various peoples around the world, and their potential (if yet to be realised) autonomy has broken the old links that kept the world under control. Whereas in Kant’s day, his philosophy could take on the language of a hegemonic universalism, able to establish itself in “abstractly universal human” terms, thinkers since have not had the same luxury (Saffari, 2019, pg.289). Levinas, for example, fought a losing battle when he argued that “the postcolonial is nothing but an attack of particularisms against the universal” (Diagne, 2020, pg.23). In actual fact, as Diagne says, “the real target [for the post-colonial] is an out-of-date universalism whose discourse is nostalgia for a time when it was permissible to serenely view Europe alone as the stage of history where the drama of the universal was being performed – a drama that could then be expanded, by colonization, to the rest of the world” (Diagne, 2020, pg.23). The old human may have died, but the hope for the decolonial project is that the formerly colonised can actively take part in creating a new human via dialogue and their own historical and cultural resources. As Dabashi put it: “The only way we can overcome one sovereign, self-conscious worldliness is for the…‘non- Western’ worlds…to become conscious of their own worldliness” (Dabashi, 2012, pg.332). The task has been set by Paolo Freire: “Apart from inquiry, apart from the praxis, individuals cannot be truly human. Knowledge emerges only through invention and reinvention, through the restless, impatient, continuing, hopeful inquiry human beings pursue in the world, with the world, and with each other. (Freire, 1974, pg.58)”